(untitled) (Research, Society and Development, 2021)
Many sectors have benefited from Virtual Reality (VR) technology, such as industries in the application of engineering design review processes. It is widely used in operator training, architecture, engineering, education, simulation and prototyping, as it provides a high level of immersion and fidelity in the representation of information. The current context of the integration between Computer-Aided Design (CAD) and VR presents development and maintenance methods that are too complex, requiring manual interventions making the transfer of information difficult, expressing an immature state of technology. Given this scenario, this work proposes a methodology for integration of CAD and VR floor plans through a software architecture that makes it possible to process the union between the technologies automatically. An research was conducted for related works in order to obtain the state of the art and the technologies in current use, in addition to pointing out the contribution of the proposed methodology. A case study was applied to electric power substations in a Research and Development (R&D) project. Integration tests, Virtual Environment (AV) reconstruction and performance tests were executed. The methodology showed good results as with the integration of CAD floor plans and the Virtual Reality software. In this paper, it is demonstrated that it is possible to adapt the two-dimensional CAD space for representation in a three-dimensional AV, facilitating and improving the design process of virtual substations. Also, the reconstruction process showed a satisfactory performance, completing the tasks in shorter times without manual interventions.